2013
DOI: 10.1007/s00774-013-0536-8
|View full text |Cite
|
Sign up to set email alerts
|

Fructus Ligustri Lucidi (FLL) ethanol extract increases bone mineral density and improves bone properties in growing female rats

Abstract: Osteoporosis is a chronic disease affecting millions of people worldwide. It is generally accepted that acquisition of a high peak bone mass (PBM) early in life can reduce the risk of osteoporosis later in life. The aims of this study were to investigate the effects of Fructus Ligustri Lucidi (FLL) ethanol extract on bone mineral density and its mechanical properties in growing female rats and to explore the underlying mechanisms. The rats were given different doses of FLL extract mixed with AIN-93G formula (0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 30 publications
5
18
0
Order By: Relevance
“…The decrease of CaBP-9k mRNA expression in kidney of OVX mice was effectively inhibited (p50.01) by FLL treatment alone. Similar results were found in duodenal CaBP-9k expression of aged female rats (Zhang et al, 2008) and growing rats Lyu et al, 2014) upon to FLL treatment. In addition, the modulation of FLL on renal CaBP-9k expression contributed to the recovery of CaBP-9k expression level in the combination treatment group, as highcalcium diet alone did not produce any change of renal CaBP9k expression in OVX mice ( Figure 1B).…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…The decrease of CaBP-9k mRNA expression in kidney of OVX mice was effectively inhibited (p50.01) by FLL treatment alone. Similar results were found in duodenal CaBP-9k expression of aged female rats (Zhang et al, 2008) and growing rats Lyu et al, 2014) upon to FLL treatment. In addition, the modulation of FLL on renal CaBP-9k expression contributed to the recovery of CaBP-9k expression level in the combination treatment group, as highcalcium diet alone did not produce any change of renal CaBP9k expression in OVX mice ( Figure 1B).…”
Section: Resultssupporting
confidence: 84%
“…The reduction in expression of renal CaSR in OVX mice in response to either FLL or high-calcium intake contributed to observed decrease of urinary calcium excretion, similarly the combination of FLL with high-calcium intake produced promising improvement on urinary calcium level of OVX mice which resulted from the synergetic effect on the regulation of renal CaSR shown in this study. The present study reported the regulation of FLL on CaSR, even though there is emerging evidence to demonstrate its regulation on calcium-transporting proteins Lyu et al, 2014;Zhang et al, 2008). Thus, the present results provided us with a clue that the potential effects of FLL on CaSR in parathyroid gland need to be further explored to explain the observed increase of serum PTH level as described previously (Dong et al, 2012).…”
Section: Resultssupporting
confidence: 74%
“…Simultaneously, the actions of WF-EE on calcium balance of DOP mice contributed to the recovery of trabecular bone micro-architecture, which was in agreement with the observed improvements of FLL extract on bone properties of growing rats (Lyu et al, 2013;Feng et al, 2014). This study provided the evidences for the potential application of FLL in managing bone health of diabetic patients, especially those with high risk of bone loss, independent of controlling blood glucose.…”
Section: Wf Dop Consupporting
confidence: 89%
“…The results of the present study also demonstrated that daily FLL ethanol extract treatment decreased the levels of inflammatory cytokines in serum in rats with LDH. Previous studies have also demonstrated that FLL promotes bone development with increased mineral density and improved bone mechanical properties (16,17). It is hypothesized that bone development in response to FLL treatment may benefit LDH treatment.…”
Section: A B C F E Dmentioning
confidence: 99%